Effects of exercise on blood pressure and arterial stiffness in patients with type 2 diabetes mellitus: a literature review - Moura, Mirian Rebeca Alves; Bezerra, Paula Taysa da Rocha; Medeiros, Melyssa Lima de; Silva, Rodrigo Marcel Valentim da (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Diabetes mellitus type 2 increases the mortality and the risk of premature morbidity related to cardiovascular disease. High blood pressure stands out as the main morbidity in this diabetic patient and arterial stiffness by one of the common complications associated with the disease, both of which can precipitate the occurrence of vascular disorders. In this context, the physical exercise is considered an important component in the treatment of these patients, as it helps in the control of cardiovascular risk factors. Objective: To investigate the effects of the physical exercise on pressure and arterial stiffness in patients with type 2 Diabetes mellitus. Methods: This is a literature review conducted in the period March-April 2015 in MEDLINE, LILACS, SciELO, PubMed and Cochrane databases. The keywords used were “Type 2 Diabetes Mellitus”, “Exercise”, “Arterial Stiffness” and “Arterial Pressure”, combined by the boolean operator “and” being considered for this review only studies published between 2009 and 2015. Results: A total of 146 publications, were select 8 studies that investigated the effects of physical exercise on blood pressure and arterial stiffness in patients with type 2 Diabetes mellitus. Of these, 6 studies investigated the effects of physical exercise on blood pressure, which was completed in 4 of them, that it was effective in promoting protective effects of blood pressure. With respect to arterial stiffness, analyzed in four studies, it was found that aerobic training was able to generate reductions in their values after 3 months of intervention, which however were not maintained after longer periods. Conclusion: The physical exercise can be appointed as a promising strategy for arterial pressure control in patients with diabetes mellitus type 2. With regard to arterial stiffness, it is assumed that structural vascular changes manifested in the disease process present irreversible characteristics and therefore can not be modified even after long periods of intervention.